PBL-based E-module Enhances 7th-Grade Cognitive Learning Outcomes: E-modul berbasis PBL Meningkatkan Hasil Belajar Kognitif Kelas 7 - Az Zakiyah, Khadijah; Wulandari, Fitria Eka (Indonesian Journal of Education Methods Development, 2024)
This study explores the impact of a PBL-based e-module on the cognitive learning outcomes of 7th-grade students at SMP Negeri 2 Krembung. Using a quantitative pre-experimental design with a one-group pretest-posttest setup, the research assessed 304 students, with 99 in the sample. A cognitive essay test measured outcomes via valid C1-C6 indicators, and data analysis employed N-Gain and one-way ANOVA methods. Results showed a moderate N-Gain score of 0.4, indicating a positive effect of the e-module. However, the one-way ANOVA indicated no significant difference in outcomes across classes. This study underscores the potential of PBL-based e-modules in enhancing cognitive learning but highlights the need for further exploration regarding outcome variances among classes. Highlight: PBL and e-modules boost 7th-grade cognitive learning. Quantitative design, N-Gain show e-module effectiveness. Research highlights class outcome variations, suggests optimization strategies. Keyword: PBL, e-module, cognitive learning, 7th-grade students, educational impact